Circular Economy, Ethical Funds, and Engineering Projects - Konstantakopoulou, Foteini (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This special issue provides a collection of 15 papers with modern theories and applications for circular economy, engineering projects, entrepreneurship models, and investor decisions. After the commencing review on Occupational Health and Safety Management-Systems Standards, follow papers which can be classified into four categories which cover the overall scope of special issue. The first category includes papers regarding the micro-level of circular economy. This means case studies in firm-level which implement different techniques to achieve sustainable development and circular economy goals. The findings reveal interesting achievements which are associated with cultural characteristics of the countries these case studies have been conducted. The second category of papers refers to the meso-level of circular economy where firms cooperate with each other by exchanging byproducts and organizing common operational procedures and routines to address environmental problems. The findings suggest assessment information technology tools to support industrial symbiosis among European firms. The next body of literature encompasses macro-level where circular economy techniques are implemented at a country level. Findings suggest methodologies for implementing and tracking circular economy in cities. Finally, a number of papers are included that focus on advanced engineering techniques. These techniques are useful tools for achieving circular economy and sustainability.